Diglossia as a Symbolic Capital in Bangladesh: A Bourdieun Analysis - Md. Mozaffor Hossain; Kaniz Fatema (Journal Corner of Education, Linguistics, and Literature, 2022)
French sociologist and public intellectual, Pierre Bourdieu’s (1930-2002) Linguistic Capital, one of his Symbolic Capitals, vividly connects with the reality and motto of the use of diglossia in Bangla language. Concurrently, this study seeks to analyze the Bangladeshis’ use of various forms of diglossia in the light of Bourdieu’s symbolic capital. It aims to elaborate how the diglossic forms of Bangla language are shaped as per both the Bangladeshi speaker’s and listener’s symbolic capitals – social capital, cultural capital, and linguistic capital; how language form reveals one’s whole power, position, status and money in the society; and how, in Bangladesh, the differences in a person’s general behavioral pattern or assumptions toward other persons about their social position can be spotted through the use of diglossia of Bangla language. The study applied a simple random sampling to conduct a survey on 50 Bangladeshis aging 18-50 years from across the country. It used the qualitative research methodology which utilized a semi-structured questionnaire to collect data, and it analysed the collected data through coding, categorizing, and  percentile representations. The findings offer integral affiliations between the use of diglossia and capitalistic considerations mostly symbolical ones.